Neurotoxicity of antiretroviral therapy. (May 2013) - Upton, Charles T; Taiwo, Babafemi; Robertson, Kevin R
The neurological outcome of HIV infection has changed dramatically in the era of HAART. Despite effective suppression of plasma viral load and a substantial decrease in the incidence of HIV-associated dementia, neurocognitive impairment and peripheral neuropathy remain widespread. The neurotoxic side effects of antiretroviral (ARV) agents are among several contributing factors to this continued prevalence. Effective penetration of the CNS by ARV agents is paramount to treating neurological symptoms as well as systemic infection, but may also exacerbate the severity of drug-related neurotoxicity. The neurotoxic side effects of ARV agents vary widely between and within drug classes. The risks and benefits of combination regimens continue to evolve as more effective treatment protocols are developed.